Dampak Supervisi Akademik Terhadap Peningkatan Kinerja Guru: Sebuah Kajian Literatur - Maharani, Mareta (Journal of Innovation in Teaching and Instructional Media, 2024)
One strategy to support the improvement of teacher performance is through academic supervision, which functions as a professional guidance process, as well as continuous evaluation of teacher learning practices. This article aims to systematically review the literature related to the impact of academic supervision on teacher performance in various educational contexts. Through the literature review method, this article identifies various aspects of academic supervision, such as frequency, methods, and approaches, which have been shown to influence its effectiveness on teacher performance. Literature findings indicate that effective academic supervision can improve pedagogical competence, managerial skills, and teacher motivation in carrying out tasks. However, this effectiveness is greatly influenced by the quality of supervision, supervisor skills, and adaptation of supervision to the needs of individual teachers. This study is expected to provide in-depth insights for practitioners and policy makers in optimizing academic supervision as an instrument for improving teacher performance in schools.